2020
DOI: 10.1002/yea.3458
|View full text |Cite
|
Sign up to set email alerts
|

PSK1 coordinates glucose metabolism and utilization and regulates energy‐metabolism oscillation in Saccharomyces cerevisiae

Abstract: Energy‐metabolism oscillations (EMO) are ultradian biological rhythms observed in in aerobic chemostat cultures of Saccharomyces cerevisiae. EMO regulates energy metabolism such as glucose, carbohydrate storage, O2 uptake, and CO2 production. PSK1 is a nutrient responsive protein kinase involved in regulation of glucose metabolism, sensory response to light, oxygen, and redox state. The aim of this investigation was to assess the function of PSK1 in regulation of EMO. The mRNA levels of PSK1 fluctuated in conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…PSK is a novel plant peptide growth regulator discovered in recent years that has a very wide range of biological activities and effects. It has been reported that PSK genes promote cell division, cell differentiation, and somatic cell formation, coordinate the metabolism and utilization of glucose, help resist oxidative stress, increase chlorophyll contents, improve salt tolerance and high-temperature tolerance of Arabidopsis, and promote the development of pear pollen tubes, and these genes are considered chemical caretakers of plant cell development processes [ 38 , 39 , 40 ]. A combined analysis of all the samples in the current study indicated that PSKS1 was the most stably expressed candidate reference gene and that VBP was the least stably expressed candidate reference gene.…”
Section: Discussionmentioning
confidence: 99%
“…PSK is a novel plant peptide growth regulator discovered in recent years that has a very wide range of biological activities and effects. It has been reported that PSK genes promote cell division, cell differentiation, and somatic cell formation, coordinate the metabolism and utilization of glucose, help resist oxidative stress, increase chlorophyll contents, improve salt tolerance and high-temperature tolerance of Arabidopsis, and promote the development of pear pollen tubes, and these genes are considered chemical caretakers of plant cell development processes [ 38 , 39 , 40 ]. A combined analysis of all the samples in the current study indicated that PSKS1 was the most stably expressed candidate reference gene and that VBP was the least stably expressed candidate reference gene.…”
Section: Discussionmentioning
confidence: 99%